Clinical characteristics and prognosis of patients with microvascular angina: an international and prospective cohort study by the Coronary Vasomotor Disorders International Study (COVADIS) Group. (26th May 2021) - Shimokawa, Hiroaki; Suda, Akira; Takahashi, Jun; Berry, Colin; Camici, Paolo G; Crea, Filippo; Escaned, Javier; Ford, Tom; Yii, Eric; Kaski, Juan Carlos; Kiyooka, Takahiko; Mehta, Puja K; et al.
Abstract: Aims: To provide multi-national, multi-ethnic data on the clinical characteristics and prognosis of patients with microvascular angina (MVA). Methods and results: The Coronary Vasomotor Disorders International Study Group proposed the diagnostic criteria for MVA. We prospectively evaluated the clinical characteristics of patients according to these criteria and their prognosis. The primary endpoint was the composite of major cardiovascular events (MACE), verified by institutional investigators, which included cardiovascular death, non-fatal myocardial infarction, non-fatal stroke, and hospitalization due to heart failure or unstable angina. During the period from 1 July 2015 to 31 December 2018, 686 patients with MVA were registered from 14 institutes in 7 countries from 4 continents. Among them, 64% were female and the main ethnic groups were Caucasians (61%) and Asians (29%). During follow-up of a median of 398 days (IQR 365–744), 78 MACE occurred (6.4% in men vs. 8.6% in women, P = 0.19). Multivariable Cox proportional hazard analysis disclosed that hypertension and previous history of coronary artery disease (CAD), including acute coronary syndrome and stable angina pectoris, were independent predictors of MACE. There was no sex or ethnic difference in prognosis, although women had lower Seattle Angina Questionnaire scores than men ( P < 0.05). Conclusions: This first international study provides novel evidence that MVA is an important health problem regardless of sex or ethnicity that a diagnosis of MVA portends a substantial risk for MACE associated with hypertension and previous history of CAD, and that women have a lower quality of life than men despite the comparable prognosis. Graphical Abstract: